PENGGUNAAN MODEL PEMBELAJARAN MAKE A MATCH SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN IPAS - Sumaiya, Sumaiya; Munirah, Munirah; Iskandar, Karmila (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2024)
AbstractThis research aims to improve student learning outcomes in science and science learning by using the make a match model in class IV at SDN 3 Limboto. This research was conducted in class IV at SDN 3 Limboto using classroom action research. Classroom action research aims to improve and enhance the quality of learning. Learning is carried out in 2 cycles. Each cycle has stages, namely: planning, implementation, observation and reflection. The subjects of this research were 38 class IV students at SDN 3 Limboto. Data collection techniques were carried out using observation and test techniques. The data analysis technique used in this research is descriptive statistics. Student learning outcomes before implementing the make a match learning model had not yet reached the KKTP. After implementing the make a match learning model student learning outcomes increased, it can be seen from the increase in completeness in the pre-cycle, 30%, increasing in cycle I to 50% and in cycle II increasing to 86% Thus, student learning outcomes and analysis of observation observation sheets improve for the better with the implementation of the make a match learning model.Keywords: Make A Match Learning Model, Student Learning Outcomes, IPASAbstrakPenelitian ini bertujuan untuk meningkatkan hasil belajar siswa pada pembelajaran IPAS dengan menggunakan model make a match di kelas IV SDN 3 Limboto. Penelitian ini dilakukan di kelas IV SDN 3 Limboto dengan menggunakan penelitian tindakan kelas. Penelitian tindakan kelas bertujuan untuk memperbaiki dan meningkatkan mutu pembelajaran. Pembelajaran dilakukan dalam 2 siklus. Setiap siklus mempunyai tahapan yaitu: perencanaan, pelaksanaan, pengamatan dan refleksi. Subjek penelitian ini adalah siswa kelas IV SDN 3 Limboto yang berjumlah 38 orang. Teknik pengumpulan data dilakukan dengan menggunakan teknik Observasi dan tes. Teknik analisis data yang digunakan dalam penelitian ini yaitu statistic deskriptif. Hasil belajar siswa sebelum diterapkan model pembelajaran make a match belum mencapai KKTP Setelah diterpkan model pembelajaran make a match hasil belajar siswa meningkat, dapat dilihat pada peningkatan ketuntasannya di pra siklus 30% meningkat di siklus I menjadi 50% dan di siklus II meningkat menjadi 86% Dengan demikian, hasil belajar siswa dan analisis lembar observasi pengematan meningkat kearah yang lebih baik dengan diterapkannya model pembelajaran make a match.Kata Kunci: Model Pembelajaran Make A Match, Hasil Belajar Siswa, IPAS.